Sintesis Li1,37Mn2O4 Dengan Metoda Solid-State Reaction dan Hidrothermal (Synthesis of Li1,37Mn2O4 by Using Solid State Reaction and Hydrothermal Methods) - Wigayati, Etty Marti; Purawiardi, Ibrahim (Jurnal Metalurgi, 2018)
Li1.37Mn2O4 as cathode on Lithium ion battery has been synthesized by SSR (solid-state reaction) and HT (hydrothermal) methods. The starting materials used were Li2CO3 and MnO2 for SSR method, with a calcination temperature of 700 oC and a sintering temperature of 900 oC. For the HT method, the starting materials used were LiOH and MnO2, at temperature of 200 oC for 90 hours duration. XRD (x-ray diffraction) pattern of SSR sample shows that spinel cubic structure of Li1.33Mn1.667O4 and FCC (face-centered cubic) structure of LiMn2O4 occurs. For the HT sample, the phases that were formed are spinel cubic structure of Li1.37Mn2O4 and Mn3O4. We can see from the TEM (transmission electron spectroscopy) images, the sample which was synthesized by SSR method, the crystallite of spinel structure resembles to that of elongated multi-walled nanofiber, while the sample fabricated by HT method formed a multi-walled ring. The SEM (scanning electron microscopy) images show that most of the particles have both elongated and roundish ellipsoidal morphology and also distributed homogeneously. From the PSA (particle size analyzer) it can be seen that the sample synthesized by SSR method has particle size of 1278.3 nm, while the sample produced by HT method has particle size of 643.7 nm. Results of cathode battery test of Li1.37Mn2O4 with the use of battery cycler are shown in the cyclic voltammetry curve which provides information on oxidation-reduction reactions. The charge-discharge measurement result shows that for Li1.37Mn2O4 (SSR), the charge and discharge capacity are 86.63 mAh/g and 85.98 mAh/g, respectively. These values are higher than those of Li1.37Mn2O4 sample fabricated by HT method which has charge capacity of 66.7 mAh/g and discharge capacity of 59.8 mAh/g.